Cytokinins Enhance Sugar-Induced Anthocyanin Biosynthesis in Arabidopsis - Das, Prasanta Kumar (Korea Society for Molecular and Cellular Biology, 2012)
In higher plants, the regulation of anthocyanin synthesis by various factors including light, sugars and hormones is mediated by numerous regulatory factors acting at the transcriptional level. Here, the association between sucrose and the plant hormone, cytokinin, in the presence of light was investigated to elucidate cytokinin signaling cascades leading to the transcriptional activation of anthocyanin biosynthesis genes in Arabidopsis seedlings. We showed that cytokinin enhances anthocyanin content and transcript levels of sugar inducible structural gene UDP-glucose: flavonoid 3-O-glucosyl transferase (UF3GT) and regulatory gene PRODUCTION OF ANTHOCYANIN PIGMENT 1 (PAP1). Genetic analysis showed that cytokinin signaling modulates sugar-induced anthocyanin biosynthesis through a two-component signaling cascade involving the type-B response regulators ARR1, ARR10 and ARR12 in a redundant manner. Genetic, physiological and molecular biological approaches demonstrated that cytokinin enhancement is partially dependent on phytochrome and cryptochrome downstream component HY5, but mainly on photosynthetic electron transport. Taken together, we suggest that cytokinin acts down-stream of the photosynthetic electron transport chain in which the plastoquinone redox poise is modulated by sugars in a photoreceptor independent manner.